Electrical resistivity and magnetization study on LaFe2As2, La0.8Ba0.2Fe2As2, and La1-xBaxPt0.1Fe1.9As2 (x=0, 0.05, 0.2, 0.4, and 0.6) superconducting compounds - BOYRAZ, CİHAT (My University, 2022)
We report the magnetic properties of LaFe2As2, La0.8Ba0.2Fe2As2, and La1-xBaxPt0.1Fe1.9As2 (0 <= x <= 0.6) compounds prepared by solid-state reaction in a wide temperature range of 5-300 K in a field up to 9 T. All as-prepared samples act as superconducting magnets at low temperatures under normal atmospheric pressure. The magnetic state of LaFe2As2 has been studied in detail in a temperature range of 5-200 K for the fields in between H = +/- 1 T. We conclude that the samples are made up of a large number of smaller and similar magnetic domains developed by the thermal agitation under the internal magnetic field during the cooling process. Considering LaFe2As2 as a parent compound, it is assumed that substituting of Ba2+ to the site La3+ results in hole doping similar to K doping in Ba1-xKxFe2As2. We have investigated the magnetic properties of La1-xBax Pt0.1Fe1.9As2. The paramagnetic contribution to the magnetization is determined by fitting the M (H, 5 K) curve using the Langevin function for each sample. Then, from the paramagnetic subtracted M-H curves, the critical current density, J(c), and normalized pinning force F-p/F-p,F-max as a function of the applied field is obtained. Moreover, the normalized pinning force density, F-p/F-p,F-max, curves versus h = H/H-irr (H-irr is the irreversibility field) were scaled using the Dew-Hughes model. Hence, the nature of the flux-pinning centers is revealed. Based on the results obtained from these analyses, we claim that the superconductivity in all as-prepared samples occurs on the domain boundary with the filamentary character and bulk superconductivity inside the domains.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Natural Sciences; Engineering and Technology; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; FİZİK, UYGULAMALI; Temel Bilimler (SCI); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; PHYSICS, APPLIED; PHYSICS; Natural Sciences (SCI); Metals and Alloys; Materials Chemistry; General Engineering; Statistical and Nonlinear Physics; General Materials Science; Engineering (miscellaneous); Electrical and Electronic Engineering; Physical Sciences; Iron-based superconductors (FeSC); diamagnetism; magnetization; resistivity; critical current density; pinning forces in superconductors; CRITICAL-CURRENT-DENSITY; BA-CU-O; PHASE-DIAGRAM; TEMPERATURE; TRANSPORT; DEPENDENCE; CRYSTALS; CREEP; FIELD; PEAK